Novel characterization discoveries of ferroptosis-associated molecules in COAD microenvironment based TCGA data - Baldi, Salem; He, Yun; Ivanov, Igor; Sun, Yaping; Feng, Wei; Refat, Moath; Mohammed, Shadi A. D.; Adlat, Salah; Tian, Zixuan; Wang, Yi; Gao, Yaping; Tian, Hui (Frontiers in Molecular Biosciences, 2022)
Background and Objective: One of the most recent forms of programmed cell death, ferroptosis, is crucial in tumorigenesis. Ferroptosis is characterized by iron-dependent oxidative destruction of cellular membranes following the antioxidant system's failure. However, it is unknown whether ferroptosis-related genes (FRGs) are associated with colon adenocarcinoma (COAD) metastasis, immune cell infiltration, and oxidative stress in COAD. The current study concentrated on FRGs expression in colon cancer metastasis, their relationship to immune cell infiltration (ICI), and potential pathological pathways in COAD. Methods and Results: Clinical information and mRNA expression patterns for patients with COAD metastasis were obtained from the public TCGA. Patients with low mRNA levels showed good overall survival than patients with high mRNA levels. The genomic-clinicopathologic nomogram was subsequently created by combining risk score and clinicopathological features. Absolute Shrinkage and Selection Operator have shown a 4 gene signature that can stratify cancer patients into high-risk versus low-risk. These four FRGs were found to be significantly linked to the overall survival of COAD patients and predicted high risk score. Next, age, stage, and PTNM were combined in univariate and multivariate cox regression models to perform a filtering procedure. The receiver operating characteristic (ROC) and calibration curves indicated that constructed signature model exhibited high prediction accuracy and clinical relevance in COAD. ARID3A showed a strong negative correlation with a wide range of immune tumour-infiltrating cells in COAD microenvironment. According to the single sample gene set enrichment analysis (ssGSEA) results, FRGs are involved in variety of pathological pathways including PI3K-AKT-mTOR pathway, reactive oxygen species (ROS) pathway, response to hypoxia pathway, and other inflammation related pathways. Moreover, dysregulation of FRGs in COAD patients showed a significance correlation with wide range of miRNAs and transcription factors(TFs). Conclusion: We identified new diagnostic biomarkers and established prognostic models for ferroptosis related programmed cell death in COAD metastasis. FRGs may improve tumor cell survival by activating the TGFB pathway, which can stimulate ROS production, accelerates ECM breakdown, and promote tumor progression and invasion. Genes implicated in ferroptosis, as revealed by the KM and a genomic-clinicopathologic nomogram, are potential therapeutic targets and prognosis indications for metastasis COAD patients.